Orthopedic Traumatology An Evidence-Based Approach (Springer International Publishing, 2018)
Now in its revised and expanded second edition, this comprehensive, user-friendly text brings the latest evidence to bear on the diagnosis and management of orthopedic trauma patients. Centering on clinical scenarios, each chapter is based on a specific case. Leaders in the field of orthopedic trauma provide their expert opinions on management strategies and techniques while using data as their guide. The book is divided into sections covering the spine, upper and lower extremities, hip and acetabulum, foot and ankle, polytrauma, infection and perioperative management. New chapters in this edition discuss elbow fracture dislocations, femoral neck fractures in the young, Lisfranc injuries and acute post-operative infection. Each chapter describes and summarizes the data in a consistent structure, but achieves this objective in a case-based format. Utilizing the latest literature, Orthopedic Traumatology: An Evidence-Based Approach, Second Edition will continue to serve as a guide for orthopedic residents and practicing physicians alike.